Comparison of PCR (Polymerase Chain Reaction) Results Using DNA Template Isolation Results with Column and Resin Methods: Perbandingan Hasil PCR (Polymerase Chain Reaction) Menggunakan DNA Template Hasil Isolasi dengan Metode Column dan Resin - Apriliana, Dinda; Mushlih, Miftahul (Indonesian Journal of Innovation Studies, 2021)
DNA isolation is a basic technique in molecular biology where DNA is separated from various unnecessary components. There are various methods of DNA isolation but the most commonly used methods are column and resin methods. The purpose of this study was to compare the results of PCR using DNA template isolated by column and resin methods. The research method used in this research is descriptive experimental using 8 whole blood samples. Samples were tested quantitatively with UV-VIS spectrophotometer and qualitatively using PCR. This research was conducted from February to April 2021. The results showed that based on quantitative DNA testing, DNA samples isolated using the column method had higher purity than the resin isolation method, which means that the resin method contained a lot of contamination. However, in terms of concentration, the resin method had a higher concentration than the column method and there was no significant difference in the purity and concentration of DNA if the sample was isolated using the column method and the resin method (r=0.169, r=0.252) after the dependent T test was performed. . In the analysis using PCR, samples isolated by the column method showed a fairly clear band compared to the resin method.